EMPOWERING LEADERSHIP AND ORGANIZATIONAL CULTURE IN RELATION WITH EMPLOYEE WELLBEING - Singh, Simran; Mahapatra, Mamata; Kumar, Navin (International Journal of Psychosocial Rehabilitation, 2020)
The present study examines the potential for empowering leadership and organizational culture to favourably influence employee wellbeing. Total of 138 professional employees working in the banking and IT/ITES sectors in Delhi/NCR were explored. Correlation and multiple regression analysis were applied to check the relationship and effect of the variables. Results show that empowering leadership and organizational culture have a significant and positive impact on employee wellbeing. This research will help managers and policymakers to create a more supportive workplace for employees.